Changing the land use from degraded pasture into integrated farming systems enhance soil carbon stocks in the Cerrado biome - Freitas, Igor Costa de; Alves, Matheus Almeida; Pena, Arlen Nicson Lopes; Ferreira, Evander Alves; Frazão, Leidivan Almeida (Acta Scientiarum. Agronomy, 2023)
Integrated agricultural production systems can increase soil organic carbon stocks over time and contribute to the mitigation of climate change. The present study aimed to evaluate soil carbon stocks, accumulation rates (TOC), total nitrogen (TN), and the quality of soil organic matter (SOM) after the transition of a low-productivity pasture into agrosilvopastoral systems in the Cerrado biome. We evaluated an 11-year-old experiment, and the treatments studied were: Eucalyptus + buffel grass; Eucalyptus + cowpea; Eucalyptus + pigeon pea; eucalyptus + buffel grass + cowpea; Eucalyptus + buffel grass + pigeon pea; Eucalyptus in monoculture (with a 20 × 3 m tree arrangement and no cultivation between rows but with a history of forage and grain crop production); and a low-productivity pasture as additional treatment and reference to the soil condition previously the land-use change. In this study, TOC and TN stocks and accumulation, labile (LC) and non-labile carbon (NLC), and SOM humic fractions were evaluated at 0-10, 10-20, 20-40, and 0-40 cm depth layers. Integrated farming systems have increased TOC and TN, NLC, carbon contents and stocks in SOM chemical fractions in all depths and TOC and TN accumulation of 5.22 Mg ha-1 year-1 and 0.23 Mg ha-1 year-1, respectively, at the 0-40 cm depth layer. The integration of Eucalyptus with legumes or buffel grass increased the LC content in the surface layer of the soil. The transition from low-productivity pasture into integrated farming systems can promote the recovery of SOM and soil quality. Hence, our results suggest that agrosilvopastoral systems can be used as sustainable farming systems in the Cerrado biome.